Planning of the amount of trains needed for transportation by rail - Jonaitis, Jonas (Transport, 2007)
The article analyses the importance of planning process of rail transportation. Railway planning problems are presented in this paper. Planning the railways for years, months, weeks or days ahead leads to substantially different problems; in this regard railway planning problems can be strategic, tactical, operational and short‐term. Another way to classify railway planning problems is based on their target: they concern the timetable, the rolling stock and the crew. Planning the structure and volume of the rolling stock is a key factor in achieving maximum efficiency of transportation by rail as well as forecasting the demand for these transport facilities. The demand for trains is a time‐dependant variable which in each case should be determined by two main approaches. The first method allows us to determine quantitative parameters of rolling stock (i.e. kilometers logged, efficiency, turnover, etc.). The second is based on specially developed mathematical models relying on qualitative characteristics such as relative expenses, efficiency of the particular train, relative expenditure of resources, cost of the trains, etc. Planning the volume of the rolling stock the determination of optimal service life of the trains plays an important role. The calculations involve repair costs, number of overhauls, current expenses and operational characteristics. First Published Online: 27 Oct 2010